The development of two Point of Care Ultrasound stations for Objective Structured Clinical Examinations in undergraduate medical education - Good, Ryan; Wilson, Juliana; Kaine, Joshua C; Daniels, Vijay J; Desy, Janeve; Lloyd, Joshua; Sheppard, Gillian; Kolbenson, Linden; Ma, Irene WY; Au, Arthur; Olszynski, Paul (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Introduction: Point-of-care ultrasound (POCUS) is a valuable clinical skill that improves clinical care but requires substantial training. Validated assessment tools provide empirical evidence regarding trainee performance while also informing program-level evaluation. We developed two POCUS-specific stations for objective structured clinical examinations (OSCEs) to assess skill acquisition and inform best practices in undergraduate medical education.Methods: A multidisciplinary group of POCUS educators identified two POCUS applications (pleural effusion and abdominal free fluid) well suited for the undergraduate level. A modified Delphi approach was used to develop POCUS-application-specific skill checklists and global rating scale. Two medical programs piloted the stations to inform reliability.Results: Across two sites, 46 and 41 students participated in the pleural effusion and abdominal free fluid stations respectively. Checklists showed high internal reliability, with Cronbach’s alpha of 0.85 (95% CI 0.71-0.93) for the pleural effusion station and 0.87 (95% CI 0.74-0.95) for the abdominal free fluid station. Krippendorff’s alpha, a measure of inter-rater reliability, was also equally strong at 0.85 (95% CI 0.43-0.94) and 0.83 (95% CI 0.50-0.94) respectively.Conclusion: Both POCUS OSCE stations demonstrated good internal and inter-rater reliability. Deployment of these OSCE stations at programs with integrated POCUS curricula may help refine programming and training expectations.